Fiber Optic Network Performance Analysis With Fiber To The Home (FTTH) Architecture - Sindung Hadwi Widi Sasono; Sri Kusumastuti (Politeknik Negeri Semarang, 2023)
Prototype is a tool used as a learning medium that has the same shape and function as the original tool or unit. The use of simulator tools as a means of learning is one of the learning methods that is very well used to find out the components, functions, and how the tool or unit works. Limitations in the delivery of lecture materials regarding Optical Networks due to the absence of modules and prototypes that help the lecture process this prototype is one of the solutions that can be used in the lecture process. Testing this prototype with measurements of damping and power obtained after configuring and installing a fiber to the home network using an optical power meter. Data analysis used in the quality of service in the system is the value of attenuation and power (power link budget) in units of dB and dBm. The results of the test get a good attenuation according to the established ratio. The practicum module is an implementation after the configuration and measurement of damping so that it can be a guide for conducting fiber optic network practicum in the Telecommunication Engineering study program.